Antimicrobial Activity of Nigella Sativa Extract Against some Bacterial and Fungal Species. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Seeds of Nigella sativa have been employed for thousands of years as spice and food preservative these seeds have been used to promote health and fight disease especially in the Middle East. In this study black seed extracted with 96% ethanol and purified chromatographically by using silica gel column with different solvents. The purpose of this study is to evaluate effect of Nigella sativa purified oil fractions on some fungal and bacterial species. The antifungal results on Fusarium Solani showed that both hexane and ethanol fractions of black seed oil revealed high antifungal properties and the diameter of growth were 24 ± 2.1mm  and 28 ± 1.5 mm, while chloroform and methanol revealed moderate effect on Fusarium Solani, the diameter of growth were 30 ± 2.5mm and 37 ± 2.9mm. Fusarium Solani did not show any sensitivity for acetone, ethyl acetate and water fractions and the diameter of growth was between 40 to 44 mm. All seven fractions tested as antibacterial with Escherichia coli, Staphylococcus aurous, Klepsiella pneumonia and Enterobacter aerogene. Hexane and chloroform fractions were toxic to the Escherichia coli with inhibition zone 18.3 ± 4.3mm and 19.3±3.5 mm also these both fractions have the same effect on Klepsiella pneumonia and Enterobacter aerogenes while having the weak effect on Staphylococcus aurous with inhibition zone ranged between 8.6 - 3.3mm. Staphylococcus aurous revealed high sensitivity to ethanol fraction with inhibition zone 22.3 ± 5.4 mm in the same time acetone, ethyl acetate and water did not show any effect on bacterial spices.